Advanced techniques for power, energy, and thermal management for clustered manycores - Henkel, Jörg (Cham, Switzerland : Springer, 2018)
This book focuses on two of the most relevant problems related to power management on multicore and manycore systems. Specifically, one part of the book focuses on maximizing/optimizing computational performance under power or thermal constraints, while another part focuses on minimizing energy consumption under performance (or real-time) constraints.
También disponible en formato EPUB